Rhizoids, technicism and economism - Simons, P. (Koers, 2011)
A highly differentiated society requires integration. Dooyeweerd refers in this regard to science and technology. Intersocietal linkages play a key role in this process. They are affected, however, by technicism and economism. Rhizoids are configurations or distinct patterns of intersocietal relationships, linking activities in society to the kingdoms of material things, plants and animals. A delineated theory of rhizoids is given, especially configured as technical-economic relationships. The article defines elements of rhizoids such as flows, stows and transformations. In principle, rhizoids enable all important economic dispositions, including non-monetary ones, to be accounted for. This is important if economising is to take place within ecological limits. The presence and impacts of technicism and economism may be discerned in the shape and operation of rhizoids. An application to the treadmill problem in agricultural production for world markets is outlined. This is followed by a brief discussion of the spirit of capitalism, as reflected in technicism and economism (the earth is seen as a machine). They trigger a dialectical movement, leading to the establishment of smaller local rhizoids as alternatives to global ones. Schuurman?s plea for a paradigm shift towards seeing the earth as a garden-city offers a way of escaping from such dialectics.